Pharmacokinetic Characterization and Dose Selection of a Novel Sumatriptan Nasal Spray Formulation, DFN‐02. (9th June 2017) - Pal, Arindam; Gautam, Anirudh; Munjal, Sagar
Abstract: This 3‐way, single‐dose, randomized crossover study evaluated the pharmacokinetics (PK) and dose proportionality of 5‐, 10‐, and 15‐mg doses of intranasal sumatriptan (DFN‐02) coformulated with a permeation enhancer (DDM) in 18 healthy adults. The objective was to determine which DFN‐02 dose approximates the PK of a 6‐mg dose of sumatriptan delivered via subcutaneous injection in the deltoid muscle of the arm. Sumatriptan plasma concentrations peaked with DFN‐02 between 10 and 15 minutes postdose, declining thereafter, with a t1/2 of about 2.5 hours; mean Cmax and AUC0–∞ values increased linearly across doses. After DFN‐02 doses of 5, 10, and 15 mg, mean Cmax was 40.7 ± 14.2, 71.2  ±  22.1, and 101.0  ±  49.5 ng/mL, and mean AUC0–∞ was 49.9  ±  20.6, 87.1  ± 31.2, and 120.5  ± 53.3 ng·h/mL, respectively. The increase in sumatriptan bioavailability was less than dose‐proportional among the DFN‐02 doses studied. Based on the established PK of a 6‐mg subcutaneous sumatriptan injection (mean Tmax,  12 minutes; mean Cmax,  74  ± 15 ng/mL in the deltoid area of the arm) and the peak and time to peak sumatriptan concentrations of the DFN‐02 doses tested, a 10‐mg dose of DFN‐02 was found to be the closest match. Overall, DFN‐02 was well tolerated at doses of 5 to 15 mg, and no new safety concerns were identified.